'Sumud' as Connected Learning: Towards a Collective Digital Commons in Palestine - Howard Scott; Monaster Ujvari; Aida Mohammad Ali Bakeer; Khaled Shanaa (Journal of Interactive Media in Education)
This paper postulates how connected learning in Palestine is characterised by the metaphor of Sumud as a steadfast resistance to disruption. We propose that the metaphor of Sumud symbolises connectedness for displaced people, whose need for connected learning encompasses a cultural and critical pedagogy, heritage, and self-determination. Palestinians exist in paradoxes we explore, particularly in those who seek to remain in their homeland but also as free to travel, study and work abroad, none of which are simple. For those who stay, education equates to an attempted continuity of normal life, which is explored through discussions with higher education teachers as part of this paper’s research design. We use Sumud to symbolize connected learning grounded in a sovereign culture that displaced communities may otherwise lose. Drawing from data resulting from an Erasmus+–funded project between the UK and Palestine, we underpin a proposal for a digital commons. The digital commons is presented as a potential toolkit of decentralised online spaces for shared learning opportunities, encapsulating Sumud for connected learning among displaced people. We propose that a theoretical framework for Sumud as a metaphor for critical pedagogy must reconcile the separate constituents of safe online spaces, social aspiration, cultural sovereignty, and political displacement and that this is manifest in the toolkit.